Determination of Insulin Resistance and Dyslipidemia after treatment with selective Anti-Depressants in case of Major Depression (Indian Journal of Public Health Research & Development, 2023)
Introduction: Depression can present a plethora of symptoms, such as loss of pleasure, feelings of guilt, low selfesteem, and disturbed sleep or appetite. Selective Serotonin Re-uptake Inhibitors (SSRIs) are considered as themainstay of treatment for depression. Several studies suggest that antidepressants increase the risk of developingmetabolic complications including Insulin Resistance (IR) and dyslipidemia, thus leading to poor health outcomes.This study would provide a review of depression and IR and examine side effects of anti-depressants that are oftenused to treat depression.Material & Methods: It was a cross-sectional analytical study conducted at the Department of Biochemistry,College of Medicine and Sagore Dutta Hospital, in collaboration with Department of Psychiatry. Patients attendingthe psychiatric OPD, who are newly diagnosed as Major Depressive Disorder (MDD) orrecurrent depressivedisorder were selected. Age and gender matched healthy family members of the patients were chosen as controls.Results: Significant alteration of Body Mass Index (BMI), Hamilton Depression Scaling (HAM-D), High DensityLipoprotein (HDL) and Low Density Lipoprotein (LDL )with non-significant variation of HOMA-IR, TotalCholesterol and Triglyceride levels were found
Keywords: Major Depressive disorder, glycemic index, HOMA-IR, Dyslipidemia,SSRI